Market access and trade liberalisation in fisheries - Ahmed, Mahfuz (International Centre for Trade and Sustainable Development GenevaCH, 2006)
Explores existing constraints faced by developing countries in international fish trade (on both the demand and supply side). Examines the possible socio-economic and environmental impacts of fish trade liberalisation. Discusses how these issues have been addressed in relevant WTO agreements and the ongoing multilateral trade negotiations. Identifies a range of priority areas for action in the context of the WTO, capacity building initiatives and national policy.